2021
DOI: 10.2147/jhc.s289840
|View full text |Cite
|
Sign up to set email alerts
|

Association of Postoperative Biomarker Response with Recurrence and Survival in Patients with Hepatocellular Carcinoma and High Alpha-Fetoprotein Expressions (>400 ng/ml)

Abstract: Background: High alpha-fetoprotein (AFP) expressions (>400 ng/mL) are associated with poor oncological characteristics for hepatocellular carcinoma (HCC). However, prognosis after liver resection for high-AFP HCC is poorly studied. To investigate long-term recurrence and survival after hepatectomy for high-AFP HCC, and to identify the predictive value of postoperative incomplete biomarker response (IBR) on overall survival (OS) and recurrencefree survival (RFS). Methods: Patients undergoing curative resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
3
5
0
Order By: Relevance
“…The survival analysis in this cohort also showed that patients with high AUF1 expression had a worse prognosis, although the difference was not statistically significant ( P = .059; Figure 1F). It is well known that elevated Alpha fetoprotein (AFP) levels are associated with the poor prognosis of patients with HCC 22 . In line with this, the AUF1 expression levels in patients with serum AFP levels ≥300 ng/mL were significantly higher than for patients with serum AFP levels <300 ng/mL in both the LCI ( P < .001; Figure C) and TCGA databases ( P < .001; Figure D).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The survival analysis in this cohort also showed that patients with high AUF1 expression had a worse prognosis, although the difference was not statistically significant ( P = .059; Figure 1F). It is well known that elevated Alpha fetoprotein (AFP) levels are associated with the poor prognosis of patients with HCC 22 . In line with this, the AUF1 expression levels in patients with serum AFP levels ≥300 ng/mL were significantly higher than for patients with serum AFP levels <300 ng/mL in both the LCI ( P < .001; Figure C) and TCGA databases ( P < .001; Figure D).…”
Section: Resultssupporting
confidence: 72%
“…It is well known that elevated Alpha fetoprotein (AFP) levels are associated with the poor prognosis of patients with HCC. 22 In line with this, the AUF1 expression levels in patients with serum AFP levels ≥300 ng/ mL were significantly higher than for patients with serum AFP levels <300 ng/mL in both the LCI (P < .001; Figure S1C) and TCGA databases (P < .001; Figure S1D). Additionally, the expression levels of AUF1 mRNA were significantly higher in the tumor tissues derived from patients with HCC who had Barcelona Clinic Liver Cancer (BCLC) stage C or larger tumors than that from patients who had BCLC stage A (P = .011; Figure S1E) or smaller tumors (P = .047;…”
Section: Auf1 Is Highly Expressed In Hcc and Predicts Poor Prognosissupporting
confidence: 73%
“…A large number of studies showed that tumor size and AFP were crucial prognostic factors of HCC. [18][19][20] The similar result was also observed in this present study. When combined with tumor size and AFP, the AIAG (0.705, 95% CI: 0.655-0.755) indicated a higher rank than BCLC staging system (Table 4).…”
Section: Comparing the Accuracy Of Predicting Survival Between The Aiag And The Classic Bclc Stagesupporting
confidence: 92%
“…Sixty-five patients with HCC were divided into two groups based on their preoperative serum AFP levels. We set AFP > 400 ng/ml as the cut-off criterion, as it is considered to be associated with adverse outcomes and oncological characteristics of HCC [ 29 ]. There were 22 cases in the AFP-high group (serum AFP > 400 ng/ml) and 43 in the AFP-low group (serum AFP ≤ 400 ng/ml).…”
Section: Resultsmentioning
confidence: 99%